Goals and Benefits of Curriculum Development - Muhammad Hasan Maulana; Badrul Islam (Beginner: Journal of Teaching and Education Management, 2025)
The purpose of this study is to know the benefits and the development of the curriculum in depth with various theories of educationists, the scope of research only concerned about its benefits and purpose, this article USES qualitative method by sharing the type of literary source and library study with studied objects as a condition or fact and otherwise without manipulation, Especially in the study and analysis of the article are the objectives and benefits of curriculum development with different book sources, articles for education. So it can provide the desired representation both in theory and in fact. A qualitative approach could give the description of an above-ground theme in depth, accuracy and accuracy with a mind-system of various educationists regarding the merits and purposes of curriculum development. In terms of the purpose and benefits of curriculum development is that curriculum development is aimed at addressing the social issues that come with the flow of time. From the foregoing it can be understood there are four substantial curriculum development goals. By a new philosophical subheading with an episodic review, an ontology and an axiom in the development of the Arabic curriculum.